Analysing the Relationship Between Human Resource Agility and Entrepreneurship Using Structural Equation Modeling Approach - Mohammad Faleh Ahmmad Hunitie (Migration Letters, 2023)
Given the profound transformations observed within the technology sector, governmental bodies are endeavouring to establish a conducive framework for digital advancement. This effort involves a concentrated emphasis on cultivating digital competencies, nurturing digital leadership, and streamlining the provision of digital financial services. Human resource agility, characterized by employees’ ability to adapt, learn, and respond to dynamic business environments, has emerged as a critical factor in driving entrepreneurship. Hence, this research tried to explore the relationship between human resource agility and entrepreneurship in the directorates of the Jordanian Ministry of Digital Economy and Entrepreneurship. Through an electronic questionnaire distributed to a convenience sample, the research obtained 310 employees which constituted a response rate of 68.8% of what was sent. The analysis procedures were followed using structural equation modeling (SEM) to achieve the research objectives. The findings demonstrated that the dimensions of human resource agility, i.e., adaptability, resilience, and competency, had positive direct impacts on entrepreneurship that were measured through innovativeness, risk-taking, and proactiveness. Therefore, the implication of this research emphasized the necessity of supporting activities associated with adaptability, decision-making velocity, and employee empowerment, such as offering training and development opportunities and fostering an innovative culture. The research findings support the theories of the resource-based view and dynamic capabilities.